Assessment of fetal myocardial performance in severe early onset pre-eclampsia (EO-PET) with and without intrauterine growth restriction across deteriorating stages of placental vascular resistance and links to adverse outcomes. (March 2017) - Bhorat, I.E.; Bagratee, J.S.; Reddy, T.
Abstract: Objective: To determine whether fetuses in severe early onset pre-eclampsia (EO-PET) with or without intrauterine growth restriction has cardiac dysfunction across deteriorating stages of placental vascular resistance and whether this dysfunction influences perinatal outcome. Study design: This was a prospective cross-sectional study performed in a tertiary care university medical centre. Sixty pregnant patients with severe early-onset pre-eclampsia between 27 and 32 weeks were recruited and matched with 60 patients having normal pregnancies. An analysis of cardiac function using the myocardial performance index (MPI) and early ventricular filling (E) and late active atrial contraction (A) ratios (E/A ratios) in the study group was performed compared to controls and further analysis was performed based on worsening placental vascular resistance and presence of growth restriction. Results: MPI values were increased in the pre-eclamptic group, irrespective if growth restriction co-exists, compared to controls (0.61 vs 0.38, p<0.001). Its median value progressively increased with worsening placental vascular resistance. For adverse perinatal outcome cut-off MPI values have been suggested. The E/A ratios were significantly decreased in the pre-eclamptic group compared to controls (0.66 vs 0.79, p<0.0001). No adverse outcomes were noted in the control group. Conclusion: Fetal cardiac function is significantly impaired in pregnancies complicated by severe early onset pre-eclampsia, irrespective if growth restriction co-exists and worsens with deteriorating grades of placental vascular resistance. The MPI can potentially be integrated into routine fetal surveillance techniques.